Proses Aklimatisasi Pada Pengolahan Limbah Cair Produksi Minyak Sawit Menggunakan Circulating Batch Reactor (CBR) - Christiani Widia BR Karo; David Andrio; Nina Veronika (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Palm Oil Mill Effluent (POME) is highly polluting wastewater with high chemical oxygen demand (COD) and biochemical oxygen demand (BOD) in which can caused severe pollution to the environment, typically pollution to water resources. On the other hand, POME was identified as potential source to generate renewable bioenergy through anaerobic digestion. Anaerobic processes need seeding and acclimatization so the microorganism could be adapted. The acclimatization process used circulating batch reactor with worked volume 25 L and glucose and sequential waste ratio of wastewater 50:50 and 0:100 (% V/V). This research observed degradation of soluble COD and growth of VSS. Experiment results showed microbial consortium has been able to adapt to the new environment and degrade organic matter along with increasing waste volume ratio and decreasing glucose volume ratio.Keywords: Acclimatization, circulating batch reactor, Palm Oil Mill Effluent, Chemical Oxygen Demand, Volatile Suspended Solids